47. PSYCHO-ARTISTIC IN THE MALAYSIA ISLAMIC PAINTINGS CONTAINED QUR’ANIC VERSES - Mohamed, Sallehuddin; Mokhtar, Mumtaz; Wan Mohamad Daud, Wan Samiati Andriana; Mudzafar, Nabilah (Journal of Islamic, Social, Economics and Development, 2024)
The field of art known as psycho-artistic examines the psychological aspects of how people perceive and react to paintings and other artistic phenomena. Sometimes it is known as psychedelic art or psychedelia. Therefore, visual art appreciators of the varied cultural backgrounds (education, interest, religion, and ethics) perceive Islamic artworks differently. It is involved in the perception of artworks and the response to artistic phenomena of the paintings. The paintings have optical illusions due to the creativity of the artwork presentation. They attracted the eyes of the art appreciators, who pondered the visual art and resulted in the perception of the object in the paintings. The human eyes and the faculty of mind (‘aql) have freedom of imaginative interpretation of the paintings’ design and contents. The visual art language created the perception or optical illusion of some viewers and formed a look-alike of any things that come to their mind. It can be considered the feeling of human eyes transmitted to the faculty of mind (‘aql) in the creativity of abstract art or viewing the aesthetic of fine art in imaginary calligraphy.